ACCOUNTING OF EXPENDITURES ON FINANCING TERRITORIAL COMMUNITIES IN TIMES OF WAR - Н. Є. Скоробогатова; К. В. Петренко; Т. В. Іванова (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
The article analyses the statistical data on the volume of budget expenditures for financing the socio-economic development of communities in Ukraine. Based on the analysis of statistical data for the last eleven years, the main trends are identified. The economy of our country had a significant social orientation: social expenditures in 2010 amounted to almost 30% of total budget expenditures. The main components of social expenditures include the following elements: social protection of pensioners, healthcare, social protection of military personnel and others. War leads to a decrease in business activity, which reduces tax revenues to the budget. Loss of jobs and lower incomes also lead to a reduction in tax revenues as a revenue stream. The destruction of enterprises and other business entities, as well as residential buildings, reduces the ability to generate revenues for the state and local budgets. This is a significant loss of expenditures to finance social and other needs of local budgets. These factors lead to a growing need to find additional sources of funding and a transparent mechanism for their accounting and audit. Military operations require the prompt introduction of new technologies for the smooth management and accounting of expenditures, and active cooperation with state, international and local organisations will contribute to effective financial management and increase the resilience of communities in difficult conditions. Accordingly, this requires improving the mechanism of accounting for the costs of financing local communities. In particular, the authors propose the following measures: introduction of modern accounting IT solutions, increasing the level of transparency and reporting of actually spent funds, improving the skills of accounting personnel, improving the regulatory framework by updating regulations in line with international standards and international experience, strengthening the role of internal and external audit of expenditures, involving citizens in the financial management process through open budget discussions with communities.